In Vivo Characterization of a Bank Vole-Derived Cowpox Virus Isolate in Natural Hosts and the Rat Model - Weber, Saskia Carola; Jeske, Kathrin; Ulrich, Rainer; Imholt, Christian; Jacob, Jens; Beer, Martin; Hoffmann, Donata (Viruses, 2020)
Cowpox virus (CPXV) belongs to the genus Orthopoxvirus in the Poxviridae family and is endemic in western Eurasia. Based on seroprevalence studies in different voles from continental Europe and UK, voles are suspected to be the major reservoir host. Recently, a CPXV was isolated from a bank vole (Myodes glareolus) in Germany that showed a high genetic similarity to another isolate originating from a Cotton-top tamarin (Saguinus oedipus). Here we characterize this first bank vole-derived CPXV isolate in comparison to the related tamarin-derived isolate. Both isolates grouped genetically within the provisionally called CPXV-like 3 clade. Previous phylogenetic analysis indicated that CPXV is polyphyletic and CPXV-like 3 clade represents probably a different species if categorized by the rules used for other orthopoxviruses. Experimental infection studies with bank voles, common voles (Microtus arvalis) and Wistar rats showed very clear differences. The bank vole isolate was avirulent in both common voles and Wistar rats with seroconversion seen only in the rats. In contrast, inoculated bank voles exhibited viral shedding and seroconversion for both tested CPXV isolates. In addition, bank voles infected with the tamarin-derived isolate experienced a marked weight loss. Our findings allow for the conclusion that CPXV isolates might differ in their replication capacity in different vole species and rats depending on their original host. Moreover, the results indicate host-specific differences concerning CPXV-specific virulence. Further experiments are needed to identify individual virulence and host factors involved in the susceptibility and outcome of CPXV-infections in the different reservoir hosts.